ANALISIS KEBUTUHAN AIR MINUM KELURAHAN SUNGAI SENGKUANG YANG BERSUMBER DARI SPAM IKK SUNGAI SENGKUANG - Ramadhan, Fatra (Fakultas Teknik Universitas Panca Bhakti, 2022)
In order to meet the increasing demand for clean water, PDAM Tirta Pancur Aji Sanggau needs to analyze the demand for clean water for the Sanggau area, one of them is Sungai Sengkuang sub-district area which is one of the sub-districts in Sanggau City. This is done so that the need for clean water for the people of Sungai Sengkuang Village can be fulfilled. The clean water delivery system is carried out based on the Regulation of the Minister of Public Works and Public Housing concerning the Implementation of the Drinking Water Supply System Number 27/PRT/M/2016 concerning the Implementation of the Drinking Water Supply System, therefore for a drinking water supply system it is necessary to know the amount of water demand and usage . The population growth factor is very important for the design of the development of drinking water distribution in a city to determine its total demand. This study aims to determine the analysis of drinking water needs in SPAM IKK Sungai Sengkuang for the next ten years. Analysis of water demand in SPAM IKK uses population rate calculations, determines population projection methods, standard deviation and population projections. The projection method used in this study is the geometric, arithmetic and exponential methods. The results of calculating the total need for drinking water in Sungai Sengkuang Village based on population projections for 2021 and 2030 are 9.057 liters/second and 10.001 liters/second with a production capacity of up to 80 liters/second. So the needs for the next 10 years from 2021 to 2030 are still sufficient for Sungai Sengkuang Village. So that it is necessary to optimize the facilities and infrastructure as well as the performance in the Sengkuang River water treatment. Keywords: Drinking water needs, Projected population, SPAM IKK